Gigantic genomes of salamanders indicate that body temperature, not genome size, is the driver of global methylation and 5‐methylcytosine deamination in vertebrates. (1st May 2022) - Adams, Alexander Nichols; Denton, Robert Daniel; Mueller, Rachel Lockridge
Abstract: Transposable elements (TEs) are sequences that replicate and move throughout genomes, and they can be silenced through methylation of cytosines at CpG dinucleotides. TE abundance contributes to genome size, but TE silencing variation across genomes of different sizes remains underexplored. Salamanders include most of the largest C‐values – 9 to 120 Gb. We measured CpG methylation levels in salamanders with genomes ranging from 2N = ∼58 Gb to 4N = ∼116 Gb. We compared these levels to results from endo‐ and ectothermic vertebrates with more typical genomes. Salamander methylation levels are approximately 90%, higher than all endotherms. However, salamander methylation does not differ from other ectotherms, despite an approximately 100‐fold difference in nuclear DNA content. Because methylation affects the nucleotide compositional landscape through 5‐methylcytosine deamination to thymine, we quantified salamander CpG dinucleotide levels and compared them to other vertebrates. Salamanders and other ectotherms have comparable CpG levels, and ectotherm levels are higher than endotherms. These data show no shift in global methylation at the base of salamanders, despite a dramatic increase in TE load and genome size. This result is reconcilable with previous studies that considered endothermy and ectothermy, which may be more important drivers of methylation in vertebrates than genome size.